Produksi Protein Sel Tunggal dari Kultur Saccharomyces cerevisiae dengan Medium Limbah Cair Tahu - Milwani Harahap; Yayuk Putri Rahayu; Minda Sari Lubis; Rafita Yuniarti (Lembaga Pengembangan Kinerja Dosen, 2024)
Single Cell Protein (PST) is the term used for proteins originating from microbes such as fungi, algae, yeast and bacteria. Tofu liquid waste is an alternative medium that has the easiest source of carbohydrates, so it has the potential for the growth of Saccharomyces cerevisiae. The aim of this research is to determine whether tofu liquid waste can produce single cell protein from S. cervisiae culture and to determine differences in protein production with the addition of nutrients to the fermentation medium. The research method used is experimental research. The independent variables are MFLT1 medium (Tofu Liquid Waste Fermentation Medium with the addition of KH2PO4 nutrients and sugar) and MFLT2 medium (Tofu Liquid Waste Fermentation Medium with the addition of KH2PO4 nutrients; (NH4)2SO4 and sugar); as well as fermentation time on days 0, 2, 4 and 6. The dependent variables are analysis of protein content, cell dry weight, glucose content, pH and temperature. The data from this research were analyzed statistically using the two way Anova method. The results of this research obtained the highest protein content in MFLT2 medium at 0.52% (day 2); cell dry weight 0.49 grams; glucose level 1.3345%; pH 5.0 and temperature 25.5 ⁰C. Meanwhile, in MFLT1 medium, the highest protein content was obtained at 0.35% (4th day); cell dry weight 0.363 grams; glucose level 1.3342%; pH 4.7 and temperature 28.8 ⁰C. From the research that has been carried out, it can be concluded that tofu liquid waste can produce single cell protein from S. cerevisiae cultures and there are differences in protein production results with the addition of nutrients to the medium, where the results of the protein content in the MFLT2 medium are higher than the protein content in the MFLT1 medium.